Effect of Health Education to Increase Students' Knowledge of Counseling - Ferdian, Dani; Hikmat, Rohman; Harahap, Saidina Malik Ibrahim; Sutanto, Himawan (Indonesian Journal of Global Health Research, 2024)
Students' mental health is a major focus in the education system, given the increasing need for attention to their mental well-being. One of the recognized strategies in strengthening students' mental health is through counseling-related health education. However, research on the impact of health education on students' knowledge of counseling is limited, particularly in the secondary school setting. This study aimed to determine the effect of health education on increasing students' knowledge about health counseling in secondary schools. This study used a quantitative research design with a quasi-experimental approach. The study sample consisted of 41 students at SMKN 36 Jakarta. The sampling technique used purposive sampling. Data were collected through the distribution of an online questionnaire that included questions about students' knowledge of the definition of counseling, counseling techniques, how to conduct counseling, the impact of counseling, and factors that affect counseling. Data analysis used univariate tests and bivariate tests using the t-test. The results of data analysis showed that health education had a significant positive effect on increasing students' knowledge of health counseling. After the health education intervention, there was a significant increase in students' understanding of the basic concepts of counseling and commonly used counseling techniques. Targeted and integrated health education programs can be an effective tool in building students' awareness and knowledge about mental health as a whole. Health education on counseling is an important step in strengthening students' knowledge on mental health.